Relationship Between Esbls Production And Virulence Factors Of Fima And Papc Gene In Uropathogenic Escherichia Coli Isolation From Private Hospital - Ade Hasan Basri; Anang Kurniawan; Joko Setyono; Dwi Utami Anjarwati (Jurnal Health Sains, 2022)
Escherichia coli is one of the opportunistic pathogenic that occupies the highest position causing the incidence of UTI. Fimbriae, particularly type 1 and P fimbriae, are the most commonly implicated bacterial cell surface virulence factors. The production of ESBL and virulence factors in E.coli bacteria causes chronicity, persistence, and recurrence of infections that cause high morbidity and mortality. Therefore, this study was conducted to explain the relationship between ESBL production and its virulence factors in E.coli bacteria. The design of this research is analytically observational with a cross-sectional approach conducted from March to May 2021. A total of 40 E. coli strains were isolated and collected from urine samples of UTI patients who were admitted to the hospital. in a private Hospital in Banyumas Region in Central Java, Indonesia. The HiChrome ESBL Agar Base media was used to screen for ESBL-Producing E. coli. Identification of firmA and papC genes was performed by using the PCR method. All urine samples diagnosed with UTI were examined for ESBL production. As many as 25% of E.coli were ESBL-production. All isolates showing positive E.coli ESBL results were then analyzed for fimA and papC genes using the PCR method. The results obtained 100% fimA gene and 80% papC gene. The conclusion is that there is a strong relationship between ESBL production with fimA and papC genes.